Product and Distribution Channel Innovation to Enhance the Growth of Islamic Financing Companies in Indonesia - Mufti, Ridho; Nurwahidin; Hannase, Mulawarman (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia, with a Muslim majority population of 87.4% and a growing trend of halal lifestyle, presents a significant opportunity for the growth of Islamic financing companies. However, the market share of Islamic financing companies remains stagnant at 5-6%, despite a significant increase in public awareness of halal products. This study aims to develop product and distribution channel innovations to enhance the competitiveness of Islamic financing companies. The research focuses on refinancing products based on the al-bai’ contract within the framework of musyarakah mutanaqishah (MMQ), which are flexible and relevant to the needs of millennials and MSMEs. Additionally, the study proposes innovations in distribution channels through the integration of financing simulations into corporate websites and mobile applications. The research methodology employs a descriptive qualitative approach, using primary data from DSN-MUI fatwas and secondary data from OJK reports. The findings indicate that Islamic refinancing innovation with al-bai’ in the MMQ framework can provide a practical solution to current limitations of Islamic products while supporting broader Islamic financial inclusion. Digital distribution channels will enhance accessibility and convenience for target markets. Implementing these recommendations is expected to expand the market share of Islamic financing companies and address the evolving needs of society